Ecoprint Batik Opportunity as an Environmentally Friendly Business (Case study: HR.Ambar Batik. Bayat, Wedi, Klaten) - Yane Puspito Sari (Institute of Computer Science (IOCS), 2022)
The textile industry is one of the contributors to the high amount of waste or garbage in the world. One of the wastes produced by the textile industry is liquid waste in the form of residual dyes/synthetic dyes from the fabric dyeing process which contains several hazardous chemical substances. In fact, initially the textile coloring process used natural dyes. However, as time goes by and technology is developing, synthetic dyes for textiles have been discovered. Natural coloring is starting to become a trend in the textile industry, especially in batik. Many batik craftsmen are getting interested in creating innovations through batik creativity by making batik using natural dyes. This natural color is obtained from leaves, flowers and even tree trunks. In this way, it is hoped that the chemical dyeing waste obtained from textile dyeing will begin to decrease. Ecoprint is one example of this natural coloring. The problems discussed are limited to the creativity of batik craftsmen to open up new opportunities by creating ecoprint batik. The expected objective of the results of this study is to find out the opportunities for batik with new environmentally friendly motifs and creativity that appears to face fashion trends. Data collection techniques and data analysis were obtained from observations, interviews, documentation and literature.